The big bang with the big brother: German unification in its third year - Horst Siebert (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
East Germany can be considered a laboratory experiment in the economics of transition. Of the three major issues in economic reforms in the transformation process — establishing an institutional infrastructure, creating monetary stability, and accomplishing adjustment in the economy, especially in the firms — two issues were solved nearly instantaneously. Monetary stabilization was achieved by extending the currency area of the deutsche mark to East Germany in the currency union of July 1, 1990. And the institutional infrastructure was, in principle, introduced at one stroke when East Germany joined West Germany, as provided for in Article 23 of the German constitution. Thus, only the third major issue of reform remains to be solved, namely real adjustment in the economy, especially in the previously state-owned firms. In the German case, transformation of a socialist economy and integration of two different economic systems are occurring simultaneously. This creates favorable conditions for eastern Germany in that western Germany can provide it with huge transfers. Thus, one could describe German unification as being the big bang with the big brother. But there are also less favorable conditions that impede the adjustment process: the exchange rate is not available as a shock absorber, and wage equalization is an important issue.
Keywords: 330; Wirtschaftliche Anpassung; Neue Bundesländer